Exit Exams Administration in Higher Education-Pre, During, and Post Exam Considerations: A Systematic Review - Samson Worku Teshome (Yayasan Almubarak Fil Ilmi, 2024)
Exit exams in higher education are a critical tool for assessing student competency and readiness for the workforce. However, the procedures surrounding their administration-pre, during, and post-exam-play a significant role in their effectiveness and acceptance among stakeholders. This systematic review synthesizes the literature on exit exam administration procedures in higher education, focusing on their design, implementation, and outcomes. Following PRISMA guidelines, a comprehensive search of electronic databases yielded 22 studies for inclusion. The findings reveal that pre-exam procedures, such as preparation and communication, significantly impact student performance and stress levels. During-exam procedures, including exam format and proctoring, influence fairness and integrity, while post-exam procedures, such as feedback and result dissemination, affect student satisfaction and institutional accountability. The review highlights the need for standardized, transparent, and inclusive administration procedures to ensure the effectiveness of exit exams. Future research should explore the long-term impacts of these procedures on student outcomes and institutional practices.